Bringing SOA to life the art and science of service discovery and design. - Deb, Manas (SOA webservices journal.)
In a service-oriented architecture (SOA), a service is a unit of work performed by a service provider to achieve desired results for one or more service consumers. A service provides a function that is well defined, self-contained (for example, loosely coupled to its environment), described solely by its interface contract and behavioral attributes (for example, it hides implementation), and located anywhere on the network.